A afetividade e o ensino de física: em busca de ações em prol da aprendizagem - Lima, Crystiano Robson de Souza (2015)
The interest of this research is to investigate the affection influence in learning physics in high school. It proposes a reflection on the role of emotions in the teaching and learning process, from the following guiding question: How the teaching of physics is influenced by affection / emotion? To understand how students conceive and characterize the teacher and the physics discipline, there were interventions, there were interventions from questionnaires and construction drawings, with high school students from a state school in the city of São Gonçalo, in the metropolitan region of Rio de Janeiro. The theorist review was based on two perspectives that overlap, namely: the theory of social representations and emotional physics, the implications of affection as a possibility of changing in the relationship between teachers and students of Physics. The Didactic Engineering was adopted as a research methodology. The results were fruitful, after the intervention, when it was realized how much the subject of this study valued the human being that is within each of the participants of the research. This time, the Educational Product, resulting from reflections on the subject, it is a support tool for teachers, proposing two questionnaires, in order to diagnose the students` social representations – related to their physics learning, the teacher's role in this process and the confidence level in solving problems of this discipline - and a drawing activity, focused on social representation as a result of the relationship between teaching and learning of physics.